Educação sexual, saúde e sexualidade: (re) significando as relações entre pais e filhos - Rapatão, Andréia Serrano Cayres [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Sexuality is inherent to human beings, besides being present from birth, in its construction, receives the influences of values, beliefs, myths and culture in which the individual is inserted, we realize that there is a cultural historical process. And this process determines the perceptions of each person in relation to their behavior, feelings, emotions, pleasure, aspects, which are also present in sexuality. In the context of sexuality also noted the difficulty in dialogue on the subject, both by teachers but also by the family. In this context, the main objective of this study was to ( re) define the relationship between the family and students, with regard to the incorporation process of sexual education, health and sexuality. The specific objectives set: identify and guide the meanings and knowledge related to sexuality and sex education in the view of family and students; contextualize the issue of sex education at school to check the conceptions of sexuality among teachers and their school practices. To achieve this research we chose the qualitative action research with socio- cultural approach and use Paulo Freire as reference. The subjects were students who were at the end of each level of education, ie, the last stage of early childhood education, 5th year of elementary school, 9th grade of elementary school II, 3rd year of high school, teachers of these levels, as well as mothers students and participating students. After collecting data, the results were described and categorized according to the similarities and particularities of each education cycle. The similarities we find the perception of adult, teacher and family, about sexuality and sex education, the importance of dialogue on issues involving sexuality, both at school and in the family, the approach on the body at each stage of development human and the sexual relationship, the importance of mediation of (a) professional to provide the proximity between the...

A sexualidade é inerente ao ser humano, além de estar presente desde o nosso nascimento, na sua construção, recebe as influências de valores, crenças, mitos e da cultura no qual o indivíduo está inserido, percebemos que existe um processo histórico cultural. E este processo determina as percepções de cada pessoa em relação ao seu comportamento, sentimentos, emoções, prazer, aspectos, que também estão presentes na sexualidade. No contexto da sexualidade ainda observamos a dificuldade em dialogar sobre o tema, tanto por parte dos professores como também pela família. Neste contexto, o objetivo principal do presente estudo foi o de (re) significar as relações entre a família e educandos, no tocante ao processo de constituição da educação sexual, saúde e da sexualidade. Como objetivos específicos, estabelecemos: identificar e orientar nos significados e conhecimentos relacionados a sexualidade e educação sexual na visão dos familiares e educandos; contextualizar a temática da educação sexual na escola para verificar as concepções da sexualidade entre os docentes e as respectivas práticas escolares. Para concretização desta pesquisa optamos pela pesquisa-ação de natureza qualitativa, com abordagem sócio-cultural e utilizamos Paulo Freire como referencial. Os sujeitos foram alunos que estavam no final de cada nível de ensino, ou seja, última etapa da educação infantil, 5º ano do ensino fundamental I, 9º ano do ensino fundamental II, 3º ano do ensino médio, professores destes níveis, além de mães de alunos e alunas participantes. Após a coleta de dados, os resultados foram descritos e categorizados de acordo com as similaridades e particularidades de cada ciclo de ensino. Nas similaridades, encontramos a percepção da pessoa adulta, professor e familiar, a respeito da sexualidade e educação sexual, a importância do diálogo nas questões que envolvem a sexualidade, tanto na escola como na...
Keywords: Sexo; Educação sexual; Família; Pais e filhos; Adolescência; Escolas; Sex